1996
DOI: 10.1007/bf02066420
|View full text |Cite
|
Sign up to set email alerts
|

The significance of elevated progesterone at the time of administration of human chorionic gonadotropin may be related to luteal support

Abstract: These data suggest that oocytes and embryos derived from patients with high preovulatory progesterone are not of a reduced quality. The association of high progesterone concentrations with a reduced rate of pregnancy varied with the type of luteal support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Some studies used logistic regression to analyze which factors were involved in PPR (14), but P level must be categorized into two groups in that method, which may magnify or minify the influence of some factors, because P level is a continuous variable. Based on these pioneer studies, four possible explanations of the occurrence of PPR were documented, i.e., multiple follicle growth (8,9), overdose of exogenous gonadotropin (14), premature lutineization (18), and poor ovarian response (19). The former three partly explain the reasons for PPR from limited facets, and the last one is not that convincing, because we found that women with lower basal FSH level were inclined to have PPR.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Some studies used logistic regression to analyze which factors were involved in PPR (14), but P level must be categorized into two groups in that method, which may magnify or minify the influence of some factors, because P level is a continuous variable. Based on these pioneer studies, four possible explanations of the occurrence of PPR were documented, i.e., multiple follicle growth (8,9), overdose of exogenous gonadotropin (14), premature lutineization (18), and poor ovarian response (19). The former three partly explain the reasons for PPR from limited facets, and the last one is not that convincing, because we found that women with lower basal FSH level were inclined to have PPR.…”
Section: Discussionmentioning
confidence: 92%
“…Some showed that PPR was associated with decreased pregnancy rate (6)(7)(8), some presented data against the negative effect of PPR (9)(10)(11), and some even reported positive correlation between PPR and pregnancy rate (12). In 2007, Venetis et al (13) published the first systematic review and meta-analysis, including 12 studies, and concluded that PPR was not associated with the probability of pregnancy.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…There have already been many papers published on this topic; however, some of them do not show a relationship between progesterone levels and pregnancy rates (Check, 1994;Bustillo et al, 1995;Levy et al, 1995;Miller et al, 1996;Venetis et al, 2007;Edelstein et al, 1990;Ubaldi et al, 1995;Silverberg et al, 1991). The latter work is a meta-analysis, which has some points of controversy like the lack of uniformity regarding the type of GnRH analogue used as well as the cutoff to define elevated serum progesterone.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis and causes of premature increase in progesterone levels are poorly understood. Several possible mechanisms are suggested, including (i) accumulated progesterone production resulting from the development of multiple follicles during controlled ovarian stimulation, with each one producing a normal amount of progesterone; (ii) overdose of exogenous gonadotrophin promoting the conversion of progesterone from cholesterol via the action of gonadotrophin on granulosa cells; (iii) premature luteinization, the consequence of a subtle increase in LH, which occurs even when GnRH analogues are used; and (iv) poor ovarian response with increased LH sensitivity . Some researchers found that exogenous gonadotrophin dose, the duration of stimulation, E 2 and LH levels on the day of hCG administration, the number of oocytes retrieved, and basal FSH level are all related with premature progesterone rise .…”
Section: Discussionmentioning
confidence: 99%